Renewable Energy IPPs in SSA – Effective use of Blended Finance - Solwa, Imraan (Graduate School of Business (GSB), 2019)
Blended finance (“BF”) is a form of structuring finance which involves using foreign aid to leverage commercial funding to a project. The topic is generally under researched, despite its increased importance in development finance and as a tool in attaining the United Nations Sustainable Development Goals. This research set out to investigate if BF was being applied in a justified manner in private sector renewable energy (“RE”) projects in Sub-Saharan Africa (“SSA”). The first two sub-questions looked at the criteria considered when qualifying projects for BF, and the factors influencing terms offered. The final sub-question was to seek operational evidence of appropriate BF usage. Data was collected through a series of semi-structured interviews with Donors, Development Finance Institutions (“DFIs”) and research institutions and analyzed using an inductive thematic approach. A descriptive case study was used to answer the final sub-question, and involved interviews with key individuals involved with the BF approval process in the selected project. The results suggest that BF is being applied in a justified manner. Sub-question one found that there is a difference in the criteria considered by Donors and DFIs when offering BF. Donor principles appear to be broader, due to their limited engagement on individual projects and delegated investment authority to DFIs. Having a development rationale and economic case for the use of BF was a prominent theme with DFIs and Donors. Factors influencing the BF terms offered to projects were difficult to extract due to the sensitive nature of the topic. Four factors did emerge, with minimizing concessionality being an overarching theme. For the final sub-question, the Mocuba Solar project was used as a case study and provided much needed evidence on the detailed processes followed in assessing the projects need for BF and how terms were derived. This research sheds light on the project level use of BF in the SSA RE IPP context and identifies areas where improvements can be made. Having more BF case studies and an agreed definition of BF for reporting purposes were recommendations to ensure BF is applied effectively.